(untitled) (AYUSHDHARA, 2024)
The conservative treatment arm includes dietary modifications, stool softeners, topical analgesics, and sitz baths. This approach focuses on symptom relief, promoting healing, and preventing recurrence. In contrast, the surgical intervention arm involves procedures like lateral internal sphincterotomy (LIS) or advancement flap repair. These techniques aim to address the underlying sphincter hypertonicity or poor blood supply to the fissure site. The case study will present two patient profiles: one managed conservatively and the other surgically. Parameters such as pain scores, healing rates, time to symptom resolution, and recurrence rates will be compared between the two groups. Additionally, quality of life metrics and patient satisfaction will be assessed. Insights from this case study can aid clinicians in selecting the most appropriate treatment modality for chronic anal fissures, considering factors such as severity, patient preference, and potential risks. Ultimately, the study seeks to contribute valuable evidence to the ongoing debate surrounding the optimal management strategy for this prevalent colorectal condition. Furthermore, the impact on the patient’s quality of life and satisfaction with the chosen treatment approach is examined. Through a multidisciplinary approach involving gastroenterologists, colorectal surgeons, and the patient, this case study highlights the importance of individualized care and shared decision-making in managing chronic fissure in ano.